Genome-Wide Identification and Co-Expression Analysis of ARF and IAA Family Genes in Euscaphis konishii: Potential Regulators of Triterpenoids and Anthocyanin Biosynthesis - Liu, Bobin; Zhu, Juanli; Lin, Lina; Yang, Qixin; Hu, Bangping; Wang, Qingying; Zou, Xiao-Xing; Zou, Shuang-Quan (Frontiers in Genetics, 2022)
Euscaphis konishii is an evergreen plant that is widely planted as an industrial crop in Southern China. It produces red fruits with abundant secondary metabolites, giving E. konishii high medicinal and ornamental value. Auxin signaling mediated by members of the AUXIN RESPONSE FACTOR (ARF) and auxin/indole-3-acetic acid (Aux/IAA) protein families plays important roles during plant growth and development. Aux/IAA and ARF genes have been described in many plants but have not yet been described in E. konishii. In this study, we identified 34 EkIAA and 29 EkARF proteins encoded by the E. konishii genome through database searching using HMMER. We also performed a bioinformatic characterization of EkIAA and EkARF genes, including their phylogenetic relationships, gene structures, chromosomal distribution, and cis-element analysis, as well as conserved motifs in the proteins. Our results suggest that EkIAA and EkARF genes have been relatively conserved over evolutionary history. Furthermore, we conducted expression and co-expression analyses of EkIAA and EkARF genes in leaves, branches, and fruits, which identified a subset of seven EkARF genes as potential regulators of triterpenoids and anthocyanin biosynthesis. RT-qPCR, yeast one-hybrid, and transient expression analyses showed that EkARF5.1 can directly interact with auxin response elements and regulate downstream gene expression. Our results may pave the way to elucidating the function of EkIAA and EkARF gene families in E. konishii, laying a foundation for further research on high-yielding industrial products and E. konishii breeding.